GAS PIPELINE DESIGN FOR DINAMIC OPTIMIZATION Case Study of Determining Optimum Compressors Placement - DJOKO DWI UTOMO (NIM : 22208307); Pembimbing : Dr. Ir. Arsegianto, M.Sc., RINALDI
Source of natural gas in Indonesia mostly located far from energy consumer centers, so that transportation system such as pipeline is needed. In transportating gas through efficient pipeline, transportation system optimization in which giving the minimum cost is needed. To minimize the total cost, the right combination of cost pipe and compressor should decided. The problems that exist in this research is how to construct an optimized gas transmission pipeline for various scenarios of gas flow rate with an increase in demand, so that the cost is minimum, but still meet the specified constraints. In this thesis, at the beginning studies is on the gas pipeline 200 km long with the total demand is 550 MMscfd, that producing for 20 years. Studies then experience the addition of a request to be joined on the gas pipeline along 100 km with a total demand of scenario 1 is 1000 MMscfd, scenario 2 is 1050 MMscfd, and scenario 3 is 1100 MMscfd. This study aims to determine the optimal solution from the use of compressor, so that gas can flow to the consumers within the tolerance of pipe strenght. This study analyze the total cost for each distance of compressor installation. Optimal Gas pipeline design for this thesis is on the gas pipeline with the installation of a compressor for scenario 1 at a distance of 20 km, for scenario 2 at a distance of 30 km, and for scenario 3 at a distance of 40 km. Selection of pipeline design is based on the smallest total cost, namely in scenario 1 is US$ 791,103,222; in scenario 2 is US$ 912,798,959; and in scenario 3 is US$ 1,151,461,968.